Improving Social Sciences Learning Outcomes Through the Picture and Picture Method: An Action Study on Junior High School Students - Mahmu'ddin Mahmu'ddin (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Introduction: The low level of student engagement and achievement in Social Studies (IPS) has raised concerns about the need for more varied and engaging teaching methods. One approach that has the potential to enhance student participation and comprehension is the Picture and Picture method, which emphasizes visual elements in the learning process. Aim: This study aims to: (1) examine the learning activities of Grade VII A students at SMPN 3 Sampit in Social Studies using the Picture and Picture method; and (2) analyze the improvement in student learning outcomes after implementing the method. Method: This research is a classroom action study using the Kemmis and McTaggart model, consisting of four stages: planning, action, observation, and reflection. The subjects were 20 students of Grade VII A at SMPN 3 Sampit. Data collection techniques included observation, testing, and documentation. Data were analyzed using percentage-based descriptive statistics to evaluate student activity and learning mastery. Results: The results showed a significant improvement in both student activity and learning outcomes. In the first cycle, 11 students achieved an activity score above 45, which increased to 18 students in the second cycle. The classical learning mastery also rose from 65% (13 students) in the first cycle to 95% (19 students) in the second cycle. Discussion: The implementation of the Picture and Picture method proved effective in fostering more interactive learning and encouraging students’ active involvement. Visualized materials made it easier to understand Social Studies concepts and stimulated students' interest in learning. Conclusion: The Picture and Picture method can enhance both learning activity and academic achievement in Social Studies among Grade VII A students at SMPN 3 Sampit. This approach is a promising alternative for implementing active, visually-based learning in junior high school Social Studies classrooms